Lipase and Its Modulator from Pseudomonas sp. Strain KFCC 10818: Proline-to-Glutamine Substitution at Position 112 Induces Formation of Enzymatically Active Lipase in the Absence of the Modulator - Kim, Eun Kyung (American Society for Microbiology, 2001)
A lipase gene, lipK, and a lipase modulator gene, limK, of Pseudomonas sp. strain KFCC 10818 have been cloned, sequenced, and expressed in Escherichia coli. The limK gene is located immediately downstream of the lipK gene. Enzymatically active lipase was produced only in the presence of the limK gene. The effect of the lipase modulator LimK on the expression of active lipase was similar to those of the Pseudomonas subfamily I.1 and I.2 lipase-specific foldases (Lifs). The deduced amino acid sequence of LimK shares low homology (17 to 19%) with the known Pseudomonas Lifs, suggesting that Pseudomonas sp. strain KFCC 10818 is only distantly related to the subfamily I.1 and I.2 Pseudomonas species. Surprisingly, a lipase variant that does not require LimK for its correct folding was isolated in the study to investigate the functional interaction between LipK and LimK. When expressed in the absence of LimK, the P112Q variant of LipK formed an active enzyme and displayed 63% of the activity of wild-type LipK expressed in the presence of LimK. These results suggest that the Pro(112) residue of LipK is involved in a key step of lipase folding. We expect that the novel finding of this study may contribute to future research on efficient expression or refolding of industrially important lipases and on the mechanism of lipase folding.